Partisipasi Wanita Muslimah Dalam Menunjang Ekonomi Keluarga (Studi Pedagang Pasar Lambocca) Kecamatan Pajukukang Kabupaten Bantaeng - Ulfa Alfiana; St. Aisyah BM; Muzdalifah Sahib (Jurnal Berita Sosial, 2024)
The aim of this research is 1) to describe the factors that encourage Muslim women to participate in supporting the family economy at Lambocca Market, Pajukukang District. 2) describe the results of Muslim women’s participation in supporting the family economy at Lambocca Market, Pajukukang District, Bantaeng Regency. The type of research that researchers use is qualitative research. This research was conducted at Lambocca Market, Pajukukang District, Bantaeng Regency, whose address is Lambocca Hamlet, Biangkeke, Pajukukang District, Bantaeng Regency. This research uses a sociological approach. Data collection techniques consist of observation, interviews and documentation. The data analysis stages consist of data reduction, data presentation and drawing conclusions. The results of the research show that 1) the factors that encourage Muslim women to participate in supporting the family economy at Lambocca Market, Pajukukang District, Bantaeng Regency, include family economy, education level, and number of family dependents. The difficulties that a working mother often faces include work problems, time management between work and the household, husband’s support, and the presence of children. 2) the results of the participation of Muslim women in supporting the family economy at Lambocca Market, Pajukukang District have helped a lot to advance the family economy, including being able to meet daily needs, having savings and several investments such as houses, land and livestock. The implication of the research is that a woman is allowed to be a wives to work in the public sector, as long as this does not make them forget and neglect their role in maintaining religious, customary and moral norms, and can fulfill the requirements and ethics of wives who work outside the home. Then, future researchers should be able to look at the position and role of women (wives) from a different perspective, because in this research the authors only describe society’s responses regarding the role of women.